Adobe Dreamweaver CC classroom in a book, 2018 release - Maivald, James J. (Classroom in a book., 2018)
Creative professionals seeking the fastest, easiest, most comprehensive way to learn Adobe Dreamweaver CC (2018 release) choose Adobe Dreamweaver CC Classroom in a Book (2018 release) from the best-selling series of hands-on software training workbooks from Adobe Press. The 12 project-based step-by-step lessons in this book show users the key techniques for working in Dreamweaver. Learn how to create webpages for the modern web with a minimum of hand coding; incorporate graphics, and text; add links to text and images; add interactive elements to your sites, such as HTML5-compatible interactivity; work with the latest HTML5 and CSS3 code and structures; and publish a finished site to the web. Four additional online lessons provide valuable hands-on experience in working with code and how to use and customize web frameworks to build a fully responsive site design to support a wide variety of desktop computers and mobile devices. The online assets also include three bonus exercises for HTML and Cascading Style Sheets, and creating web assets, essential to your understanding of web design and website development. That's 16 total lessons chock full of invaluable information and real world examples. The online companion files include all the necessary assets for readers to complete the projects featured in each lesson as well as ebook updates when Adobe releases relevant new features for Creative Cloud customers. All buyers of the book get full access to the Web Edition: a Web-based version of the complete ebook enhanced with video and multiple-choice quizzes.